High Andean regions and their socioeconomic vulnerability: the case of the urban area of Puno - Zevallos, Nancy (2023)
In recent times, the risks of disasters caused by natural events have increased as a result of climate change. The magnitude of a disaster resulting from the impact of a natural hazard on a human system depends not only on the type and intensity of the hazard, but also on the socioeconomic conditions of the community. The objective of this research was to determine the level of socioeconomic vulnerability to natural disasters in the urban area of the city of Puno, in the High Andean region of southern Peru. This was achieved by using the Analytical Hierarchical Process (AHP) technique in combination with Geographic Information Systems (GIS). A semi-structured questionnaire was applied to a random sample of 256 people. Vulnerability data was collected for five different types of hazards to which the population is exposed: floods, erosion, rockfall, landslides, and unstable soils. Fourteen indicators were used in the dimensions of exposure, fragility and resilience. As a result, a socioeconomic vulnerability map was obtained, showing levels of vulnerability corresponding to the levels of high and very high vulnerability of the peripheral areas of the study area. The findings of this research will be helpful for those in charge of policy-formulation in disaster risk-management to take informed decisions in reducing the vulnerability and increasing the resilience of the High Andean population of Puno.